Case of multisystem inflammatory syndrome in children presenting as fever and abdominal pain. Issue 9 (8th September 2020) - Mahajan, Neha; Chang, Huan Ting; Leeman, Rachel; Manalo, Rachel; Glaberson, Wendy Robin
Abstract : This case aims to remind all providers to scrutinise for atypical presentations of multisystem inflammatory syndrome in children (MIS-C) which may mimic a more routine diagnosis. In the absence of mucocutaneous symptoms, the diagnosis of MIS-C can be missed. Given the potential for rapid deterioration of patients with MIS-C, early treatment and inpatient interventions are necessary.